PENINGKATAN KETERAMPILAN PEKERJA SEKTOR KONSTRUKSI (Studi Kasus Pelatihan Tukang Pemula pada Balai Pelatihan Konstruksi Wilayah II Surabaya) - , Yudhiani Titi Sundari ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The construction sector ranks fifth in the national working population according to main job (BPS 2010). While at the regional level, East Java Province, a progress is being made, the comparison of the working population in February 2011 to February 2010, shows that there is gratest improvement in construction sector by 113,7 thousand people. The increasement in skills of construction workers to be one way of potential increasement in employment.Through the training provided, the trainees are expected to have skills and better bargaining position. This research took Beginner Training Case studies conducted by Balai Pelatihan Konstruksi Wilayah II Surabaya. The aim of this research is to determine wheter the training meet the construction workersâ need: in terms of skills and job status improvement. The research methods used are qualitative and quantitative methods. Qualitative method is done through in depth interview and FGD, while the quantitative methods is done through descriptive analysis of secondary data to support the achievement of research goals. Results showed that the training met the need of construction worker for skills enhacement based on depth interviews and analysis of related documents. However the training has not been able to the ultimate goal of training: construction workerâs welfare improvement. It is because of waging system in society that has not fully support the sertification program, the different participantâs motivation, especially for the non construction worker and the construction worker, the weakness in the selection process, and acces to employment information that has not been fully utilized, and the limitation of construction workers in accessing higher status. The recommendation offered is a more open dissemination of training, stricker selection process, and stronger cooperation with related institution, such as BLK and PJTKI.